Intergenerational family constellations in contemporary Europe: Evidence from the Generations and Gender Survey - Allan Puur; Luule Sakkeus; Asta Põldma; Anne Herm (Demographic Research, 2011)
Demographic research has drawn attention to the multiple ways in which changes in mortality and childbearing have produced major shifts in intergenerational family structures. The aim of this article is to contribute to this body of research by analysing the data from the Generations and Gender Surveys for nine European countries. In the study, data pertaining to the availability of ascending (parents and grandparents) and descending kin (children, grandchildren and great-grandchildren) of the respondent are combined to shed light on the family structures in which indviduals are embedded at various stages of their lives. The findings provide new insights into the ways in which the past and present diversity of demographic regimes comes together into specific patterns of intergenerational family constellations across Europe. This convergence may yield family constellations of very similar "height" in countries with sharply contrasting demographic histories. The results also indicate that certain demographic scenarios may halt or temporarily reverse the trend towards the further vertical extension of family constellations.